(untitled) (Contemporary Journal of Social Science Review, 2024)
Cultural hybridity has emerged as a significant theme in diasporic literature, particularly in the works of authors like Jhumpa Lahiri. This paper aims to explore cultural hybridity within the context of Lahiri’s novels, short stories, and essays. By analyzing how Lahiri’s characters negotiate their identity between two cultures—the culture of their homeland and that of their host country—this study highlights the complexities of cultural assimilation and retention. The research will investigate the manifestations of hybridity in Lahiri’s work, focusing specifically on her portrayal of second-generation immigrants, identity crises, and the intersection of tradition and modernity. Employing qualitative research methodology, this paper will critically analyze primary texts such as Interpreter of Maladies (1999) and The Namesake (2003) alongside secondary scholarly resources. By doing so, it aims to contribute to a broader understanding of how diasporic literature reflects the multicultural realities of contemporary society.